UVA and UVB Photoprotective Capabilities of Topical Formulations Containing Mycosporine-like Amino Acids (MAAs) through Different Biological Effective Protection Factors (BEPFs) - Francisca de la Coba; José Aguilera; Nathalie Korbee; María Victoria de Gálvez; Enrique Herrera-Ceballos; Félix Álvarez-Gómez; Félix L. Figueroa (Marine Drugs, 2019)
The safety and stability of synthetic UV-filters and the procedures for evaluating the photoprotective capability of commercial sunscreens are under continuous review. The influence of pH and temperature stressors on the stability of certain Mycosporine-like amino acids (MAAs) isolated at high purity levels was examined. MAAs were highly stable at room temperature during 24 h at pH 4.5–8.5. At 50 °C, MAAs showed instability at pH 10.5 while at 85 °C, progressive disappearances were observed for MAAs through the studied pH range. In alkaline conditions, their degradation was much faster. Mycosporine-serinol and porphyra-334 (+shinorine) were the most stable MAAs under the conditions tested. They were included in four cosmetically stable topical sunscreens, of which the Sun Protection Factor (SPF) and other Biological Effective Protection Factors (BEPFs) were calculated. The formulation containing these MAAs showed similar SPF and UVB-BEPFs values as those of the reference sunscreen, composed of synthetic UV absorbing filters in similar percentages, while UVA-BEPFs values were slightly lower. Current in vitro data strongly suggest that MAAs, as natural and safe UV-absorbing and antioxidant compounds, have high potential for protection against the diverse harmful effects of solar UV radiation. In addition, novel complementary in vitro tests for evaluation of commercial sunscreens efficacy are proposed.